SEISMIC INVERSION TO IDENTIFY FACIES AND POROSITY DISTRIBUTION OF LOWER TALANG AKAR FORMATION HYDROCARBON RESERVOIR. CASE STUDY: âTIMUR JAUHâ FIELD, SOUTH SUMATRA BASIN - Ramadan, Rifky
Oil and gas production in Indonesia has decreased in recent years, so it is necessary to explore/develop fields. One of the efforts made is the development of the "TIMUR JAUH" Field, Lower Talang Akar Formation (LTAF), South Sumatra Basin. The "TIMUR JAUH" field consists of 3 compartments bounded by faults and causing differences in fluid contact. There are 4 layers in this field which are bounded by the Flooding Surface (FS). The four layers are Upper, Middle, Lower, and Simpang. The lithology of the "TIMUR JAUH" Field consists of sandstone, shale, as well as a thin seam of coal. The reservoir in this field is sandstone filled with hydrocarbons and validated the presence of CO2 gas. The study was conducted using 3D PSTM (Post Stacked Time Migration) seismic data and 64 well data with 5 key wells that have the most complete data and represent the three compartments. Sensitivity analysis was carried out to separate coal, sandstone, and shale. Furthermore, AI (Acoustic Impedance) inversion is applied to seismic data and then transformed into porosity, sand/shale ratio, and CO2 distribution maps. However, there is ambiguity in the distribution of porosity and CO2, because the value of AI is also influenced by the presence of coal and fluids, and then the limited data of CO2. The results of the facies analysis show that LTAF is deposited in the transgressive phase, this is shown by the presence of thick sandstone deposits that are slowly getting thinner due to sea level rise. Analysis of isochron (ms) and isopach (ft) maps showed the thickening of sedimentation correlated with relatively high physical properties of sandstone and CO2 gases. Furthermore, the distribution of fluid shows that the hydrocarbon zone is in an area with high porosity and sand/shale ratio dominated by gas fluids. It can be concluded that the reservoir is a porous sandstone dominated by gas fluids.